(untitled) (Mugda Medical College Journal, 2025)
Growing pains (GP) are the most common form of nonspecific, recurrent leg pain syndrome in early childhood and frequent cause of paediatric outpatient visits. A case-control study was conducted at National Centre for Control of Rheumatic Fever and Heart Diseases, Dhaka, Bangladesh, from August 2021 to October 2022 to determine the relevant laboratory tests that can help diagnose growing pains among children reported hospital outpatient departments (OPD) with typical limb pains. 220 children (aged between 3 and 12 years) with non-specific musculoskeletal pain in limbs suspected of growing pains were enrolled. The controls were 200 clinically healthy children with no history of limb pain. Laboratory tests included complete blood count (CBC) with ESR, serum CRP, total calcium, phosphate, alkaline phosphatase, and rheumatoid factor. The mean age of children with growing pains was 7.88±3.2 years and boys were predominant (52.17%). Children with growing pains had marginally lower mean level of calcium (9.37±0.91 mg/dl vs. 9.52±0.93 mg/dl) and phosphorus (3.58±1.18 mg/dl vs. 3.70±1.17 mg/dl) than the controls. There were non-significant higher mean levels of CRP (2.64±1.03 mg/dl vs. 2.52±1.43 mg/dl) and alkaline phosphatase (336±161 U/L vs. 313±153 U/L) among GP children. Other parameters were within normal range according to age and sex. There were no significant differences between the results of those two groups. Therefore, we conclude that growing pains should be a clinical diagnosis. If inclusion and exclusion criteria are followed carefully, in children with limb pain typical for GP, there is no need for laboratory tests to make the diagnosis. Mugda Med Coll J. 2025; 8(2): 107-111